Elements Influencing Student Lag of the Bachelor's in English Teaching at National University - Alpízar-Alpízar , Mildred (2025)
This qualitative research with an exploratory approach was designed as a means to give voice to the students of the Bachelor’s Degree in English Teaching (BEI) who are experiencing academic lag. As a minority within the broader student population, they lack immediate mechanisms to address their situation. The main objective was to analyze the impact of various factors on the phenomenon of academic lag among BEI students at the National University.  The study presents and analyzes the socioeconomic, academic, and institutional factors influencing academic lag, based on data collected through three research techniques: (a) focus group, (b) in-depth interview, and (c) questionnaire. The results reveal the factors and reasons that, according to the participants, affected their learning process and led them to fall behind academically.  The case study concludes with two possible solutions to support this student population: (a) implementing a mentoring and support program to assist students experiencing academic lag, and (b) reviewing the methodology used for scheduling courses.